2021
DOI: 10.1111/jcal.12538
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in K‐12 and higher education: A systematic review of the literature from 2000 to 2019

Abstract: This study is a systematic review of 20 years of research on the usage of virtual reality (VR) in K‐12 and higher education settings, which aims to consolidate, evaluate, and communicate evidence that can inform both the theory and practice of VR‐based instruction. A total of 149 articles were selected from three major academic databases using search strings and manual screening protocols. The literature analysis emphasized four interrelated aspects of VR‐based instruction: instructional context, instructional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 71 publications
(87 reference statements)
6
83
1
10
Order By: Relevance
“…The immersion principle in multimedia learning (Makransky, 2021) and the cognitive affective theory of immersive learning (CAMIL; Makransky & Petersen, 2021) describe how the fundamental driver of increased learning outcomes in immersive media is the use of instructional design principles that are effective in immersive lessons. Latest research has also shown that how well IVR promotes learning is greatly dependent on how IVRspecific content has been designed (Meyer et al, 2019;Baceviciute et al, 2020;Makransky, 2021;Luo et al, 2021;Parong & Mayer, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immersion principle in multimedia learning (Makransky, 2021) and the cognitive affective theory of immersive learning (CAMIL; Makransky & Petersen, 2021) describe how the fundamental driver of increased learning outcomes in immersive media is the use of instructional design principles that are effective in immersive lessons. Latest research has also shown that how well IVR promotes learning is greatly dependent on how IVRspecific content has been designed (Meyer et al, 2019;Baceviciute et al, 2020;Makransky, 2021;Luo et al, 2021;Parong & Mayer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Use learning theories to guide IVR based application development and research (Raditanti et al, 2020); (2) Shift attention from VR technology to VR-based instructional design with a redefined focus on the effective integration of technology and theory (Luo et al, 2021); and…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It helps students better understand the behaviour of objects and the consequences of the behaviour [33]. According to research, VR technology was commonly implemented in higher education, especially in the basic science and medicine domain, in order to provide more real interactive engagement with students [34]. Nonimmersive VR and immersive VR (IVR) are the two types of virtual reality.…”
Section: • Virtual Realitymentioning
confidence: 99%
“…This has increasingly been facilitated by pervasive learning technologies, mainly involving what is frequently referred to as technology enhanced learning (TEL), usually applied in formal educational settings. Laurillard et al (2009) defined TEL as any computer-based technology used for learning, including virtual reality (Luo et al, 2021), inside and outside formal learning contexts which can be stationary or mobile, depending upon the devices being used by individuals and groups of learners. Previous researchers demonstrated that the use of TEL in different educational settings, especially online learning, resulted in changes in leadership for learning (Laferrière & Breuleux, 2002;Fisser & Phillips, 2020).…”
Section: Introductionmentioning
confidence: 99%